Influence of point mutations on the stability, dimerization, and oligomerization of human cystatin C and its L68Q variant - Szymanska, Aneta; Jankowska, Elżbieta; Orlikowska, Marta; Behrendt, Izabela; Czaplewska, Paulina; Rodziewicz-Motowidło, Sylwia (Frontiers in Molecular Neuroscience, 2012)
Human cystatin C (hCC) is a small but very intriguing protein. Produced by all nucleated cells is found in almost all tissues and body fluids where, at physiological conditions, plays a role of a very potent inhibitor of cysteine proteases. Biologically active hCC is a monomeric protein but during cellular trafficking it forms dimers, transiently loosing its inhibitory activity. In vitro, dimerization of cystatin C was observed for the mature protein during crystallization trials, revealing that the mechanism of this process is based on the three dimensional swapping of the protein domains. In our work we have focused on the impact of two proposed “hot spots” in cystatin C structure on its conformational stability. Encouraged by promising results of the theoretical calculations, we designed and produced several hCC hinge region point mutation variants that display a variety of conformational stability and propensity for dimerization and aggregation. A similar approach, i.e. rational mutagenesis, has been also applied to study the amyloidogenic L68Q variant to determine the contribution of hydrophobic interactions and steric effect on the stability of monomeric cystatin C. In this overview we would like to summarize the results of our studies. The impact of a particular mutation on the properties of the studied proteins will be presented in the context of their thermal and mechanical stability, in vitro dimerization tendency as well as the outcome of crystallization. Better understanding of the mechanism and, especially, factors affecting conformational stability of cystatin C and access to stable monomeric and dimeric versions of the protein opens new perspectives in explaining the role of dimers and the domain swapping process in hCC oligomerization, as well as designing potential inhibitors of this process.